MHD natural convection in a wavy nanofluid enclosure with an internally corrugated porous cylinder - Nehad Abid Allah H.; Fawzi Sh. Alnasur; Ammar Abdulkadhim; Isam Mejbel Abed; Nejla Mahjoub Said; Azher M. Abed (Journal of Taibah University for Science)
The present work focuses on investigating magnetohydrodynamic (MHD) natural convection in a complex I-shaped enclosure with corrugated walls, filled with nanofluid and porous media layers. This study analyzes various parameters' effects on heat transfer and fluid flow. The enclosure's left and right walls maintain low temperatures, while the other walls are insulated. The inner corrugated cylinder experiences high temperatures. The study examines the impact of Rayleigh number (Ra), Hartman number (Ha), nanofluid volume fraction (ϕ), Darcy number (Da), MHD inclination angle (γ), position of the corrugated cylinder (δ) and number of undulations (N) on isotherms, streamlines, velocity profiles and average Nusselt number variations. The results show that higher Ra values increase the average Nusselt number while increasing Da enhances it by 65%. Magnetic source inclination greatly affects heat transfer, with Nusselt at γ = 90° being 15.34 compared to 10.234 at γ = 0°. The study concludes that optimal heat transfer occurs at γ = 90°, Ra = 106, Da = 10−3, Ha = 30 and N = 2.